Imobilização e caracterização de lipases para reações de transesterificação - Barão, Carlos Eduardo (2012)
The lipase from Thermomyces lanuginosus and Bacillus sp. ITP-001, free and immobilized in sol-gel matrices produced with TMOS and TEOS precursors in the presence of different additives and dried by the techniques of xerogel vacuum desiccator and aerogel supercritical CO2 was used in the transesterification of vegetable oil to determine the influence of these factors on the reaction. Initially free lipase enzyme was characterized by its hydrolytic and transesterification activities, giving the results of 504.4 U mg-1 and 1233.79 U g-1 at 37 ºC and it was found that lower temperatures give higher values of activities within the range studied. Further, when the free enzyme was used for the production of ethyl esters via a factorial design, it was found that lower temperatures (37 °C) and lower molar ratios of oil:ethanol (1:6) gave again the highest yields in esters, but temperature is the only factor of influence with 95 % confidence. In a second step the influence of moisture content was verified for the immobilized lipase with TEOS, dried as aerogel with PEG additive and through a factorial design 22 (varying moisture content and temperature), and it was found that higher moisture content (30 %) and lower temperatures (40 °C) provided the highest values of transesterification activity and that both factors, as their interaction, were influencing factors, with 95 % confidence. The biocatalyst at these conditions gave values of surface area of 502.4 m2 g-1, pore volume of 0.643 cm3 g-1 and average pore diameter of 51.18 Å. In the next step it was verified the influence of additive (ionic liquid) on the immobilization with TEOS xerogel and aerogel with enzymes from Thermomyces lanuginosus and Bacillus ITP 001. In this case high yields of immobilization were obtained as 232.4 % and 243.3 % for the ITP 001 enzyme and 83.9 % and 111.7 % for the enzyme from Thermomyces dried as xerogel and aerogel, respectively. The values of hydrolytic and transesterification activities at 37 °C were superior for the ITP enzyme and comparing the two types of drying studied, the aerogel provided higher values of activity. The characterization by BET technique demonstrated a greater surface area, pore volume and pore size in aerogel preparations for both enzymes and also gave greater surface roughness for biocatalyst particles of this type of drying. Finally, it was verified then the influence of the silica precursor (TMOS and TEOS) on the biocatalysts dried by the xerogel and aerogel techniques. The results of hydrolytic activity, esterification and transesterification at 37 °C again demonstrated the superiority of the aerogel preparations that gave high values for the transesterification activities with biocatalysts having TEOS as precursor, while for the other two types of activity studied it was observed superiority of the TMOS precursor. In characterizing by the BET technique the highest values for surface area and pore volume were obtained for xerogel prepared with TEOS (contradictory results to those obtained previously) and all preparations were composed of mesopores. The biocatalysts obtained were further characterized by SEM (demonstrating the roughness and material retained on surfaces of products) and by DSC and TGA, in which it was observed the behavior of the preparations with increasing temperature, observing defined stages of mass loss and heat flux. These preparations were also used in the production of ethyl esters under the conditions of mass amount of enzyme of 7.5 % relative to the mass of oil, at 37 °C and molar ratio oil:ethanol 1:9 for all preparations. Under these conditions, there was a much higher ester yield for the preparation using TMOS, particularly for that dried as xerogel compared to the precursor TEOS in both drying. The largest relative yields observed (as compared to the precursor TMOS and drying xerogel) were obtained in times of 48 h for drying xerogel with precursor TEOS (44%) and TMOS aerogel (60%), whereas for the TEOS precursor aerogel drying the highest yield was observed for 96 h (27 %). At the end, a cycle of reuse was performed with both biocatalysts obtained by aerogel and using reaction time of 48 h with the same conditions as initially defined and it was found that after one cycle, the precursor TMOS retained 91.4 % of its initial activity while the TEOS precursor remained with only 2.8%, confirming the high efficiency of the TMOS precur45sor in the production of ethyl esters.